THE BILINGUAL SCHOOL PROGRAM MANAGEMENT - Prayitno, Eko; Hadi, Sutarto; Saleh, Muhammad (Journal of K6, Education and Management, 2019)
The existence of bilingual junior high schools is very limited, government schools are at the state high school of Paringin 4 and non government schools are one of them, Middle School Al Mazaya of Banjarmasin. The purpose of the study is to get an overview of: Planning, implementing, evaluating, following up and constraining the bilingual program in the school. This research is a qualitative descriptive study with a case study approach. The Conclusion: First, the school runs a plan in accordance with the Leading function, the plan is in accordance with the school's objectives. Second, private schools have the freedom to implement the program. Third, evaluation of bilingual schools has the same goals and patterns, differences in frequency of evaluation. Fourth, the follow-up of the program is to establish a bilingual high school. Fifth, the constraints of bilingual schools are not all students can follow bilingualism well. Suggestion: Relevant educational agencies should provide opportunities for teachers to participate in international linguistic forums, Principals should develop a language certification program for teachers and staff, teachers always develop themselves in terms of language, further researchers to focus on one aspect of management.